2014
DOI: 10.1021/ef502162b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Vacuum Resid and Its Fractions by Fourier Transform Ion Cyclotron Resonance Mass Spectrometry with Various Ionization Techniques

Abstract: Venezuela Orinoco extra-heavy-crude-oil-derived vacuum resid (VR) was subjected to supercritical fluid extraction and fractionation (SFEF) to prepare multiple narrow fractions. The SFEF fractions were analyzed by Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) with various ionization techniques, including positive-ion electrospray ionization (ESI), negative-ion ESI, positive-ion atmospheric pressure photoionization (APPI), and sulfur methylation followed by positive-ion ESI. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 46 publications
(74 reference statements)
0
34
0
Order By: Relevance
“…Recently, FT-ICR MS with different ionization techniques has been applied to identify molecular composition of complex hydrocarbon mixtures because of its ultra-high resolution [13][14][15] . Electrospray ionization (ESI) and atmospheric pressure photoionization (APPI) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 are commonly used as the ionization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, FT-ICR MS with different ionization techniques has been applied to identify molecular composition of complex hydrocarbon mixtures because of its ultra-high resolution [13][14][15] . Electrospray ionization (ESI) and atmospheric pressure photoionization (APPI) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 are commonly used as the ionization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies , by coarse-grained methods, but the chemical structures represented by beads cannot be clearly identified. ,, Guan et al utilized the structural unit and dissipative particle dynamics (SU-DPD) method to simplify the molecules in the SARA heavy-oil system, in which each kind of bead represented a specific basic unit. In this paper, we employed their methods of beads division and the content of SARA components in the system; the structure of asphaltene was obtained by atomic force microscopy (AFM) and the structure of the resin, aromatic, and saturate molecules were constructed by Venezuelan vacuum residue composition analysis data based on Zhang et al The beads used and their corresponding chemical structures are listed in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…112 Qian et al 38 further reported a wide diversity of petroporphyrin structures that contain multiple sulfur and oxygen atoms (CcH2c+zN4VOoSs) in vacuum residue using APPI FT-ICR MS. 38 The first comprehensive characterization of vanadyl porphyrins in unfractionated heavy petroleum and virgin asphaltenes using APPI FT-ICR MS was performed by McKenna et al 31 The authors highlight the need for FT-ICR MS to achieve unambiguous molecular formula assignment (˂300 ppb) and document the likelihood of misassigning vanadyl porphyrin peaks (N4O1 51 Vanadyl porphyrins have been detected in asphaltenes isolated from vacuum gas oil distillate cuts and in pentane, in-between C5C7 asphaltenes, and heptane asphaltenes using APPI FT-ICR MS. 113,114 Additional studies have applied APPI FT-ICR MS to asphaltene extrography fractions and highlight structural characterization using infrared multiphoton dissociation (IRMPD), confirming the dominance of single core vanadyl porphyrin structures. 84 Supercritical fluid extraction and fractionation (SFEF) of Venezuelan Orinoco extra heavy crude vacuum residue concentrates vanadyl porphyrins in high boiling end cuts detected using APPI FT-ICR MS. 66 Furthermore, Chacón-Patiño et al 115 investigated the molecular composition of vanadyl porphyrins in PetroPhase 2017 asphaltenes and extrography fractions, with a specific focus on the molecular composition of vanadyl porphyrins as a function of the aggregate size distribution, using GPC ICP-MS and online GPC APPI FT-ICR MS at 21 tesla (Figure 5). The authors performed quantitative detection of vanadium using GPC ICP-MS and concluded that the majority of the vanadyl porphyrin ions are produced from later eluting GPC fractions (low aggregation LMW part) and that highly aggregated fractions contain abundant porphyrins with much longer homologous series than those species from the less aggregated GPC fractions.…”
Section: ■ Ionization Techniques For Ms Of Metalloporphyrinsmentioning
confidence: 99%